Boric acid incorporated on the surface of reactive nanosilica providing a nano‐crosslinker with potential in guar gum fracturing fluid. Issue 27 (7th March 2017) - Zhang, Zifeng; Pan, Hao; Liu, Peisong; Zhao, Mengyun; Li, Xiaohong; Zhang, Zhijun
ABSTRACT: Small molecule borate crosslinker widely used in hydraulic fracturing treatment has a low crosslinking efficiency of less than 1%. Thus boric acid was introduced onto the surface of reactive nanosilica (denoted as nano‐SiO2 ; size: about 20 nm) containing NH2 group to obtain a nanosilica‐based crosslinker (denoted as nano‐crosslinker) with increased crosslinking efficiency, thereby broadening the application of nano‐SiO2 in guar gum fracturing fluid. Moreover, the influence of the as‐prepared nano‐crosslinker on the rheological behavior of guar gum gel was investigated with borate crosslinker as a reference. Results show that boric acid chemically reacts with the amino group of the reactive nano‐SiO2 to form NB bond, which is beneficial to the formation of the network structure of guar gum gel. The guar gum gel crosslinked with the 57 ppm of borate based on the carrier of nano‐SiO2 exhibits better temperature tolerance and shear resistance as well as breaking behavior than the counterpart crosslinked with 200 ppm of borate. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45037. Abstract :